2019
DOI: 10.1038/s41467-019-09986-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in S/G ratio in natural poplar variants do not predict catalytic depolymerization monomer yields

Abstract: The ratio of syringyl (S) and guaiacyl (G) units in lignin has been regarded as a major factor in determining the maximum monomer yield from lignin depolymerization. This limit arises from the notion that G units are prone to C-C bond formation during lignin biosynthesis, resulting in less ether linkages that generate monomers. This study uses reductive catalytic fractionation (RCF) in flow-through reactors as an analytical tool to depolymerize lignin in poplar with naturally varying S/G ratios, and directly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
158
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(166 citation statements)
references
References 61 publications
7
158
0
1
Order By: Relevance
“…[40][41][42][43][44][45] the low correlation between β-O-4 proportion and the relative S residue content in poplar natural variants. [46,47] Altogether, our results showed that different residues are subjected to a specific proportion of β-O-4 linkages within the lignin polymer. Positional analyses of G CHOH , S CHOH and G CHO residues moreover revealed a clear decoupling between the proportion of terminal and internal residues depending on the mutation.…”
supporting
confidence: 51%
“…[40][41][42][43][44][45] the low correlation between β-O-4 proportion and the relative S residue content in poplar natural variants. [46,47] Altogether, our results showed that different residues are subjected to a specific proportion of β-O-4 linkages within the lignin polymer. Positional analyses of G CHOH , S CHOH and G CHO residues moreover revealed a clear decoupling between the proportion of terminal and internal residues depending on the mutation.…”
supporting
confidence: 51%
“…G units can be additionally interlinked at their C-5 atom via β-5 or 5-5 bond [14,44]. This might mean that the distribution and linking of the monomers in Sida lignocellulose is less uniform than in the other two plant biomasses.…”
Section: Compositional Analysis Of Raw Materials and Organocat Productsmentioning
confidence: 99%
“…The environment is suffering from climate change, worsened by over-exploitation of resources thus increasing global greenhouse gas emission (Anderson et al, 2019;Hassan et al, 2019). Sustainable and environmentally friendly energy based on renewable resources are required in order to meet the world's future energy needs.…”
Section: Introductionmentioning
confidence: 99%